Changes in Online Shopping Behavior for Ready-Made Clothes among Saudi Consumers following COVID-19 - Al-Zahrani, Areej Saleh; Al-Dabbagh, Maha Abdullah (Journal of Humanities & Social Sciences, 2023)
This study emphasizes the influence of the environment, society, and individual characteristics on consumer behaviour, particularly among Saudi individuals who possess their own customs, traditions, values, and perceptions of clothing purchasing decisions. However, technological advancements, specifically the Internet, have played a role in exposing Saudi society to the cultures of other societies, and influencing consumer behaviour. This study focuses on understanding the factors that have led to a shift in consumer behaviour towards online clothing shopping in the Kingdom of Saudi Arabia following the COVID-19 pandemic. The research aims to contribute to knowledge about the post-pandemic behaviour of Saudi consumers, specifically in terms of increased online purchases of ready-made clothes, and align with the goals of the Kingdom’s Vision 2030, which aims to foster a thriving economy. The study employs a descriptive analytical approach. The study population consists of Saudi consumers in general across the Kingdom of Saudi Arabia, and a random sample of 125 individuals aged 18-47 and above was selected to complete the questionnaire. The key findings from the study highlight that consumers prefer online shopping due to the convenience, time and effort savings, ease of ordering, and wide range of choices in terms of clothing models and colours. Online purchasing is also perceived as more cost-effective, offering discounts and coupons that physical markets may not provide. Based on these findings, the study recommends enhancing the accuracy of clothing product descriptions on dedicated online platforms for selling clothes. Additionally, it suggests diversifying the clothing options available in local markets to cater to different tastes and age groups and creating websites specifically for local markets.